The Effectiveness of Entrepreneurship Learning by Using Integrated Entrepreneurial Film-Based Media on Students' Learning Achievement - Sudarwati, Ninik; Prianto, Agus (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2021)
This study aimed to measure the effectiveness of entrepreneurship learning by using integrated entrepreneurial film-based media on students' learning achievement. This study employed a quasi-experimental method with one group pre-test-post-test design by comparing the results of pretest and posttest and statistically analyzed the t test formula. The participants involved were 400 students from STKIP PGRI Jombang, STKIP PGRI Tulungagung, STKI PGRI Nganjuk, and UNWAHA Jombang. Findings suggest that there was an average difference of -4.41 with pretest (21.80) and posttest (26.21) results. Meanwhile, the standard deviation was 5.42, and the t value was 16.268. Besides, the probability value or sig (2 tailed) was 0.00 <0.05. It can be concluded that Ho is rejected, and Ha is accepted. In conclusion, this study proved that entrepreneurship learning by using integrated entrepreneurial film-based media is effective.